Subtitling Strategies in Wednesday The Series - Auliana Dania Zulfa; priska meilasari (Universitas Katolik Widya Mandala Surabaya, 2025)
This research investigates the application of Gottlieb’s (1992) subtitling strategies in the Indonesian subtitles of the first episode of the Wednesday series. The study aims to identify which of the ten proposed strategies—expansion, paraphrase, transfer, imitation, transcription, dislocation, condensation, decimation, deletion, and resignation—are utilized and how frequently they appear. Using a qualitative descriptive method, the researcher analyzed 40 subtitle data points and found that eight out of ten strategies were employed. The most dominant was the transfer strategy (10 instances), indicating a preference for literal translation that maintains the original meaning without alteration. Paraphrase (8 instances) and condensation (7 instances) followed, suggesting the translator's effort to adapt the content for better cultural accessibility and readability. Expansion (5 instances) and transcription (4 instances) were also used to clarify cultural references and preserve speaker identity. Meanwhile, decimation (3), deletion (2), and resignation (1) were applied less frequently due to translation challenges or irrelevance. Imitation and dislocation were not observed in the data. Overall, the study concludes that the subtitling of Wednesday reflects a balanced approach between faithfulness to the source text and pragmatic adaptation, adhering to the norms and constraints of audiovisual translation.